2015
DOI: 10.1080/17441692.2015.1057091
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring health researchers globally: Diverse experiences, programmes, challenges and responses

Abstract: Mentoring experiences and programmes are becoming increasingly recognised as important by those engaged in capacity strengthening in global health research. Using a primarily qualitative study design, we studied three experiences of mentorship and eight mentorship programmes for early career global health researchers based in high-income and low- and middle-income countries. For the latter, we drew upon programme materials, existing unpublished data and more formal mixed-method evaluations, supplemented by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 36 publications
4
80
0
Order By: Relevance
“…Both of these strategies have been applied in the CHESAI PDRFs, as discussed in the findings, whereby we were attached to projects through which we gained practical experience of researcher–practitioner engagement and we were involved in teaching and student co-supervision alongside our mentors in the form of apprenticeship. Cole et al [25] also identified mentorship as crucial for capacity strengthening in health research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these strategies have been applied in the CHESAI PDRFs, as discussed in the findings, whereby we were attached to projects through which we gained practical experience of researcher–practitioner engagement and we were involved in teaching and student co-supervision alongside our mentors in the form of apprenticeship. Cole et al [25] also identified mentorship as crucial for capacity strengthening in health research.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence where, in some developed countries, fellows have been able to use a PDRF to establish networks and find employment [2224]. On the other hand it has been reported that fellows in developing countries (although similar incidents reported elsewhere) have also experienced some negative effects of the PDRF including lack of committed mentorship [25]. …”
Section: Introductionmentioning
confidence: 99%
“…The mentee also needs to be able to accept constructive feedback, corrections and even failures, and take a proactive role in managing their research project/research career. Some key strategies for sustaining a mentor‐mentees relationship are outlined in Table 1 8, 9, 11, 12, 13…”
Section: Getting the Most Out Of The Mentor‐mentee Relationshipmentioning
confidence: 99%
“…3 Arguably a key strategy is ensuring clinicians have access to research mentors. [7][8][9] Mentoring is more than just supervision, and achieving effective mentoring requires numerous factors, and can be enhanced by mentor training. [8][9][10] Mentoring busy clinicians to develop research skills and capacity requires a unique understanding of clinical pressures and workforce limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Mentoring as an interprofessional concept has grown in popularity as a means for achieving research productivity and academic success (Byrne Keefe, 2002; Cole et al, 2015; Conn, Porter, McDaniel, Rantz, Maas., 2005; Haddi, Lindquist, Buckwalter, 2013; Kubiak, Guidot, Trimm, Kamen, Roman, 2012; Mass et al, 2006; Morrison-Beedy, Aronowitz, Dyne, Mkandawire, 2001; Schrubbe, 2004; Travis Anthony, 2011; Yin et al, 2015). The National Advisory Committee (NAC) of the Nurse Faculty Scholars (NFS) program, which was charged with shaping this Robert Wood Johnson Foundation commitment to the development of junior nursing faculty, saw mentoring as a means of “increasing cultural capital” for sustainable academic success (Chanderbhan-Forde, Heppner, Borman, 2012) and of decreasing levels of role conflict and role ambiguity (Specht, 2013) and looked to it as the key component in building the capacity of nursing science.…”
mentioning
confidence: 99%